Corporate governance : management vs. external auditors. - Lim, Seng Kok. (2008)
Our studies have led us to focus the two key players responsible for synthesising an effective internal control system in a company: the management and the externalauditors. We picked the shareholders to assess who, between them, is more effective in ensuring that these proper internal controls are in place.